Detection of Salmonella sp in pork carcasses in slaughterhouses in Lima, Peru - Salvatierra R., Guillermo (2015)
The aim of this study was to detect the frequency of Salmonella sp by isolation techniques in pork carcasses intended for human consumption. Three hundred carcasses from two slaughterhouses in Lima, Peru were studied. Samples were taken by swabbing the skin of the head, abdomen, back and leg, representing 1200 subsamples. They were taken to the laboratory in Falcon tubes with buffered peptone water, and processed following the protocol for isolation of bacteria based on ISO 6579:2002. The isolates were identified by biochemical tests and specific antisera. In 6.3 ± 2.4% (19/300) of carcasses and 1.8% (21/1200) of subsamples were detected Salmonella sp. The highest frequencies of isolates were obtained from the head (33.3%, 7/21) and the abdomen (33.3%, 7/21). The isolates were serotyped and identified as Salmonella enterica subesp. enterica serotype Derby. The results confirm the need to implement control measures and detection of the bacteria to reduce the frequency of contaminated pork that reaches the consumer.